2020
DOI: 10.3390/ijms21239099
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Deficiency and Pharmacological Stabilization of Mast Cells Ameliorate Pressure Overload-Induced Maladaptive Right Ventricular Remodeling in Mice

Abstract: Although the response of the right ventricle (RV) to the increased afterload is an important determinant of the patient outcome, very little is known about the underlying mechanisms. Mast cells have been implicated in the pathogenesis of left ventricular maladaptive remodeling and failure. However, the role of mast cells in RV remodeling remains unexplored. We subjected mast cell-deficient WBB6F1-KitW/W-v (KitW/KitW-v) mice and their mast cell-sufficient littermate controls (MC+/+) to pulmonary artery banding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…48 For cardiac MRI recordings, similarly, the obesity of ZSF-1 obese animals made them incompatible with the bore of the machine available to us (MRsolutions MRS3017), a system already fitted to be compatible with overweight small animals. On this account, M-mode imaging of the RV in the parasternal long-axis view is the preferred method in studies featuring small animal echocardiography [49][50][51] and-given its high temporal and spatial resolution-viewed as the accepted approach to assess relative RV dimensions and function.…”
Section: Discussionmentioning
confidence: 99%
“…48 For cardiac MRI recordings, similarly, the obesity of ZSF-1 obese animals made them incompatible with the bore of the machine available to us (MRsolutions MRS3017), a system already fitted to be compatible with overweight small animals. On this account, M-mode imaging of the RV in the parasternal long-axis view is the preferred method in studies featuring small animal echocardiography [49][50][51] and-given its high temporal and spatial resolution-viewed as the accepted approach to assess relative RV dimensions and function.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of wild-type mice subjected to pressure overload by PAB with the mast cell stabilizer cromolyn significantly improved RV remodeling and function [87]. Similarly, mast cell-deficient Kit W /Kit W-v mice subjected to PAB showed minimal RV dilation and preserved RV function [87]. These beneficial changes in RV remodeling were associated with reduced gene expressions in the RV of proinflammatory cytokines, such as TNF-α and IL-6 [87].…”
Section: Mast Cells In Right Ventricular Physiology and Remodelingmentioning
confidence: 96%
“…Observations in PAB rats showed that mast cell density in the RV was significantly increased as late as 200 days following pressure overload induction [119]. The evidence for the pathological role of mast cells in adverse RV remodeling was further provided in experiments exploiting mast cell-deficient mice and pharmacological inhibition of mast cell activation [87]. Treatment of wild-type mice subjected to pressure overload by PAB with the mast cell stabilizer cromolyn significantly improved RV remodeling and function [87].…”
Section: Mast Cells In Right Ventricular Physiology and Remodelingmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, an increased content of mast cells was observed in the RV upon pressure overload in PAB mice [83]. The mast cell stabilizer cromolyn prevented and reversed RV remodeling in PAB mice when applied from day 1 or day 7 after PAB operation, respectively [84]. Furthermore, both NF-κβ and TLR9 inhibitors could improve RV remodeling, fibrosis, and function by attenuating myocardial inflammation in PAB rats [85].…”
Section: Pharmacotherapies Modulating Myocardial Inflammation and Rosmentioning
confidence: 98%